Photochemical cross-linking of influenza A polymerase to its virion RNA promoter defines a polymerase binding site at residues 9 to 12 of the promoter. - Fodor, E; Seong, B; Brownlee, G (1993)
A previous study of the 12 nucleotide-long influenza A virion RNA promoter has shown that three nucleotides, residues 9 to 11, were crucial for transcription in vitro, although other nucleotides play a significant but less important role. A model for polymerase-promoter recognition was proposed, according to which there were two sites: a binding site at residues 9 to 11 and a regulatory site at or near the site of initiation at residue 1. By studying the effect of point mutations in the promoter on the binding efficiency of the polymerase using a photochemical cross-linking assay, we now show that residues 9 to 12 are crucial for binding. In addition residues 4 to 8, though not as important, are involved in binding, possibly by stabilizing the polymerase-promoter complex. Both PB1 and PB2 apparently play an important role during virion RNA promoter recognition and binding.